Tahammul Dan Al-Ada’ Dalam Periwayatan Hadis - Isma'il (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2022)
Hadith is the second source of Islamic teachings that has received considerable attention from both Muslims and non-Muslims. Most of them accept it as a source of religious teachings, considering that it has received recognition from Allah swt. in the Qur'an, while others reject it outright. The refusal is at least due to doubts about the validity of the hadith as a track record of the actions, words, and decrees of the Prophet Muhammad. who in fact lived 14 (fourteen) centuries ago.so we need to know in what way and how the hadith was transmitted. Scholars have put forward the method of transmitting hadith, including the method of receiving (Tahammul) and conveying (Al-Ada') hadith, as well as the conditions associated with it. Tahammul is the process of receiving the narration of a hadith from a teacher with certain methods. While Al-'Ada is the process of conveying and narrating hadith.The majority of scholars tend to allow listening activities carried out by small children, namely children who have reached taklif age. While some of them do not allow it. Scholars who allow it are also still different opinions regarding the age limit for children to be accepted for transmission, the first opinion says five years while the second opinion says tamyiz.The eligibility requirements for al-Ada are: Islam, Baligh, Fairness, Dhabt. While the method in tahammul al-ada' is through several ways, namely as-sima', al-Qira'ah 'ala Shaykh, al-Ijazah, al-Munawalah, al-Mukatabah, I'lam ash-Shaykh, al-Washiyyah, al-Wijadah. This article will explain the tahammul and al-ada 'methods in the transmission of hadith as knowledge for novice readers and students in exploring and studying ulumul hadith.